Legal Protection for Consumers Engaging in E-Commerce Transactions via the Social Media Platform Instagram - Nelly, Roos (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The internet is widely utilized in various commercial activities, and trade conducted through the internet is commonly known as e-commerce. One form of internet-based trade is conducted through the Instagram platform. Trading through the social media platform Instagram gives rise to numerous legal issues along with its associated risks. One of the problems that may arise is breach of contract. The purpose of this thesis is to analyze the rights and obligations of the parties involved in sale and purchase transactions conducted through Instagram and to examine the legal consequences that arise if the seller commits a breach of contract in such transactions. The research method used is normative-empirical legal research by examining the implementation of positive legal provisions (statutory regulations) and contracts in factual circumstances in specific legal events occurring within society to achieve predetermined objectives. It also examines law as conceptualized in actual behavior, as an unwritten social phenomenon experienced by individuals in social interactions. The data sources used consist of library research and interviews. The analysis is conducted qualitatively, and the research findings are presented in narrative paragraph form, while the data are presented descriptively and analytically.